2022
DOI: 10.1161/circresaha.122.320184
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii Attenuates CKD via Butyrate-Renal GPR43 Axis

Abstract: Background: Despite available clinical management strategies, chronic kidney disease (CKD) is associated with severe morbidity and mortality worldwide, which beckons new solutions. Host-microbial interactions with a depletion of Faecalibacterium prausnitzii in CKD are reported. However, the mechanisms about if and how F prausnitzii can be used as a probiotic to treat CKD remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“… 199 Orally administered Faecalibacterium exerts both anti-inflammatory and renoprotective effects on patients with CKD through butyrate-mediated G protein-coupled receptor-43 signaling. 200 Moreover, traditional Chinese medicine has also achieved considerable progress in DKD treatment, as a combination of Huangkui capsules and irbesartan was found to be more effective than either of the medications alone in reducing albumin-to-creatinine ratio in patients with DKD, 201 suggesting the potential role of Chinese medicine in future DKD therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 199 Orally administered Faecalibacterium exerts both anti-inflammatory and renoprotective effects on patients with CKD through butyrate-mediated G protein-coupled receptor-43 signaling. 200 Moreover, traditional Chinese medicine has also achieved considerable progress in DKD treatment, as a combination of Huangkui capsules and irbesartan was found to be more effective than either of the medications alone in reducing albumin-to-creatinine ratio in patients with DKD, 201 suggesting the potential role of Chinese medicine in future DKD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We found a decreased proportion of Faecalibacterium and an increased proportion of Enterococcus in IBD patients with CDI compared with IBD-only. Faecalibacterium has been reported as a probiotic, which had anti-inflammatory potential via butyrate production and regulation of butyrate-mediated inflammatory pathways ( Roychowdhury et al., 2018 ; Zhou et al., 2018 ; Xu et al., 2020 ; Li et al., 2022a ). Depletion of Faecalibacterium has been observed in pediatric CD patients with CDI ( Hellmann et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have confirmed the role of butyrate in regulating inflammatory responses. It was demonstrated that butyrate supplemented by Faecalibacterium ameliorated macrophage infiltration and reduced the levels of Mcpt1, IL-1β, and IL-6 in chronic kidney disease [ 38 ]. In alcoholic liver disease, butyrate was also found to significantly increase the plasma IL-10 concentration while decrease the level of plasma TNF-α [ 39 ], thus alleviating the progression of liver lesions.…”
Section: Enterotype and Inflammatory Responsesmentioning
confidence: 99%